Pengaruh Motivasi Kerja, Kemampuan Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Telkom Akses Makassar - Muh. Ryan Hidayat Muhsini; Abdi Akbar; Agung Widhi Kurniawan; Chalid Imran Musa; Rezky Amalia Hamka (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to determine how the influence of work motivation, work ability, and work environment on employee performance. The number of samples used was 79 employees. Data collection was carried out using interview, observation and questionnaire methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that the quality of motivation (X1) partially has a positive and significant effect on employee performance. Ability (X2) partially provides a positive and significant influence on employee performance. The work environment (X3) partially does not have a significant effect. And simultaneously the three independent variables have a significant effect on employee performance..